(untitled) (AYUSHDHARA, 2019)
The disease which is caused by excessively aggravated Vayu (Vata) & vitiated blood (Rakta) is called Vatarakta. It is better correlated with “Gout” in the modern medical science. Vatarakta is a metabolic disorder where in pain is predominant symptom, which disturbs day to day life of the patients. Gouty Arthritis is a disorder of Purine metabolism and is an inflammatory response to the MSUM (Monosodium Urate Monohydrate) crystals, formed secondary to hyperuricaemia. The purpose of the present case study was to find out an effective and well-accepted drug for this dreadful condition of the joints which was historically known as "the disease of kings" or "rich man’s disease". So, in the present study Virechana (Shodhana) with Eranda Taila, Guduchyadhikashayam, Amrithadi Guggulu (Shaman) and Kokilakshakashayam whenever there is an acute attack of pain and swelling for a period of 30 days are selected, which are easily available, cost effective and can be easily carried out. The result is outstanding with reduced acute attacks, decrease in the symptoms and hyperuricaemia. Further clinical trials can be conducted to prove the efficacy of the drugs statistically.